Mechanisms of AAV neutralization by human alpha-defensins. - Jessica M Porter; Kaitlin R Hulce; Mackenzi S Oswald; Kevin Busuttil; Shanan N Emmanuel; Antonette Bennett; Robert McKenna; Jason G Smith (PLoS Pathogens)
Antiviral immunity compromises the efficacy of adeno-associated virus (AAV) vectors used for gene therapy. This is well understood for the adaptive immune response. However, innate immune effectors like alpha-defensin antimicrobial peptides also block AAV infection, although their mechanisms of action are unknown. To address this gap in knowledge, we investigated AAV2 and AAV6 neutralization by human neutrophil peptide 1 (HNP1), a myeloid alpha-defensin, and human defensin 5 (HD5), an enteric alpha-defensin. We found that both defensins bind to AAV2 and inhibit infection at low micromolar concentrations, similar to our prior studies of AAV6. While HD5 prevents AAV2 and AAV6 from binding to cells, HNP1 does not. However, AAV2 and AAV6 exposed to HD5 after binding to cells are still neutralized, indicating an additional block to infection. Accordingly, both HD5 and HNP1 inhibit externalization of the VP1 unique domain of both AAV2 and AAV6, which contains a phospholipase A2 enzyme required for endosome escape and nuclear localization signals required for nuclear entry. Consequently, both defensins prevent AAV from reaching the nucleus. Disruption of intracellular trafficking of the viral genome to the nucleus is reminiscent of how alpha-defensins neutralize other non-enveloped viruses, suggesting a common mechanism of inhibition. These results will inform the development of vectors capable of overcoming these hurdles to improve the efficiency of gene therapy.